Impact of Financial Literacy and Investment Experience on Risk Tolerance and Investment Decisions: Empirical Evidence from Pakistan - Awais, Mustabsar; Laber, M. Fahad; Rasheed, Nilofer; Khursheed, Aisha (International Journal of Economics and Financial Issues, 2016)
Investment decision making is a very crucial process which is influenced by many factors. An important thing which is necessary to understand is the degree to which an investor can absorb the risk. This intensity of risk which can be of minimal, maximum or mediocre level, defines the strategies regarding the decisions of investment. A determinant of investment decisions needs special consideration to be understood by investors. This paper helps to determine those variables by constructing a theoretical model. After studying the past researches and theories certain conclusions are drawn whether which are the factors that impacts the decision making process. This paper is structured as follows. The first part describes relevant literature and devises hypotheses. Section 2 describes the model, methodology, data source and the variables measurement. Section 3 is based on a discussion and concludes and provide with future implications. Keywords: Risk Tolerance, Investment Decision Making, Investment Experience, Financial Literacy JEL Classifications: G02, G11, G110